Resting time after phorbol 12-myristate 13-acetate in THP-1 derived macrophages provides a non-biased model for the study of NLRP3 inflammasome - Giambelluca, Sonia; Ochs, Matthias; Lopez-Rodriguez, Elena (Frontiers in Immunology, 2022)
Background: The activation of NLRP3 inflammasome in macrophages has been proven to play a crucial role in the development of cardiovascular diseases. THP-1 monocytes can be differentiated to macrophages by incubation with phorbol-12-myristate-13-acetate (PMA), providing a suitable model for in vitro studies. However, PMA has been shown to have effects on the levels of IL-1β, the main mediator of NLRP3 inflammasome, while the effects on the other mediators of the inflammasome have not been reported before. Methods: THP-1 monocytes were incubated without (THP-1), with 5ng/ml PMA for 48h (PMA48h) or with 5ng/ml PMA for 48h plus 24h in fresh medium (PMArest). Morphological changes and the expression of macrophage surface markers (CD14, CD11b, CD36 and CD204) were evaluated by flow cytometry. Changes in intracellular levels of inflammasome components (NLRP3, ASC, pro-caspase-1, pro-IL1b) were analyzed by western blot and release of mature IL-1β in cell supernatant was analyzed by ELISA. ASC speck formation was determined by immunofluorescence. Results: After 48h incubation with PMA or subsequent rest in fresh medium, cells became adherent, and the differential expression of CD36, CD11b, CD14 and CD204 compared to THP-1 cells confirmed that PMArest resemble macrophages from a molecular point of view. Changes in the levels were detected in PMA48h group for all the NLRP3-related proteins, with increase of NLRP3 and pro-IL-1β and secretion of mature IL-1β. In PMArest, no pro-IL-1β and lower amounts of mature IL-1β were detected. No ASC speck was found in PMA treated groups, but the addition of a second stimulus to PMArest resulted in ASC speck formation, together with IL-1β production, confirming the responsiveness of the model. Conclusion: Differentiation of THP-1 with 5ng/ml PMA followed by 24h resting period provides a model that morphologically and molecularly resembles macrophages. However, even at low concentrations, PMA induces production of IL-1β. The 24h rest period provides for down-regulation of pro-IL-1β in PMArest group, without affecting its ability to respond to a second stimulus through activation of inflammasome.